PENGARUH INTELLECTUAL CAPITAL TERHADAP PRODUKTIVITAS PADA PERUSAHAAN YANG GO PUBLIC DI INDONESIA - Jarot Santosa, Eko Meiningsih Susilowati & (Lembaga Penelitian dan Pengabdian Masyarakat, 2017)
This research is a quantitative research.The short-term goal in this study is to find out whether intellectual capital has a positive effect on productivity, while for the long-term goal is to know how much intellectual capital plays a role in improving company performance.The data used is secondary data from the annual report (annual report).Population in this research is company which go public in Indonesia which is listed in BEI.The samples are companies that go public in Indonesia listed on the Stock Exchange in 2013 until 2015, which includesinfrastructure, utilities and transportation.Sampling is done with purpose sampling.Variable used is independent variable that is intellectual capital and as dependent variable that is productivity.Data analysis using multiple linear regression.The result of this research is that there is negative influence of intellectual capital toward productivity in companies that go public in Indonesia.Keywords: intellectual capital,productivity